Predictive and prognostic significance of loss of heterozygosity in ABC transporter genes in breast cancer - Tsyganov, Matvey M.; Ibragimova, Marina K.; Garbukov, Evgeny Yu; Bragina, Olga D.; Zdereva, Ekaterina A.; Usynin, Evgeny A.; Litvyakov, Nicolay V. (Сибирский онкологический журнал)
ABC-transporter family genes have been well studied and their involvement in the development of drug resistance has been assessed. The presence of aberrant conditions in these genes can affect the treatment and prognosis of the disease. Loss of heterozygosity (LOH) is one of these conditions; it is a common event in cancer development. Therefore, the aim of this study was to investigate the relationship between LOH in ABC transporter genes in breast cancer and response to chemotherapy and disease prognosis. Material and Methods. A total of 130 breast cancer patients were included in the study. Microarray analysis was performed on Affymetrix CytoScan™ HD Array high-density DNA chips to assess LOH status. Chromosome Analysis Suite 4.1 software (Affymetrix, USA) was used to process microarray results. Results. Forty-nine ABC transporter genes were evaluated for LOH. The frequency of LOH ranged from 6.9 % to 90 %. An association analysis identified two genes: ABCG5 and ABCG8, in which the presence of LOH was associated with a lack of objective response to neoadjuvant chemotherapy. The presence of LOH in the ABCA5, ABCA6, ABCA8, ABCA9, ABCA10 and ABCC3 genes was associated with high rates of metastasis-free survival (log-rank test, p<0.04). conclusion. The presence of loss of heterozygosity in the ABC transporter genes was found to have no significant effect on the response to chemotherapy. However, a high prognostic potential of ABCA family genes was found.